Clino-Pathological Correlation of Dermatological Manifestations in People Living with HIV/AIDS (PLHIV) at a Tertiary Care Hospital, Western India - Radadiya, Poonam Chakubhai; Dholakia, Aditi Dinesh (Annals of Pathology and Laboratory Medicine, 2018)
Background: A large number of skin conditions that might present to a dermatologist ranging from infectious to benign to malignant in HIV positive patients. Many of them need detailed and time consuming investigations to confirm the clinical diagnosis. Probably skin biopsy is the most important ancillary aid to confirm the clinical diagnosis. Skin biopsies play a vital diagnostic role when different diseases present with clinically similar skin lesions. A diagnostic approach is given based on the predominant histological reaction pattern, with an emphasis on clinicopathological correlation. So, this study tries to assess the clinic-pathological correlation in dermatological manifestations in PLHIV. Methods: Punch biopsies from the skin lesions were studied from March 2016 to April 2017 with routine histopathology examination and special stains were used as and when required. Clinical diagnosis was then correlated with histopathological examination. Result: A total of 60 punch biopsies of PLHIV were studied. 22 (36.66%) patients had infectious lesions and 38 (63.33%) patients had non-infectious lesions. Correlation of Clinical diagnosis was done with histopathological findings, which showed 88.8% of papular lesions well correlated histopathologically. Only 33% of malignant and premalignant skin conditions were diagnosed correctly on clinical examination. Overall, 68.33% of cases including non-neoplastic and neoplastic lesions, showed clinic-pathological consistency. Conclusion: Skin biopsy and clinicopathological correlation is clearly a worthwhile investigative procedure.